2017
DOI: 10.1155/2017/3156534
|View full text |Cite
|
Sign up to set email alerts
|

An Insight in the Reproductive Biology of Therophilus javanus (Hymenoptera, Braconidae, and Agathidinae), a Potential Biological Control Agent against the Legume Pod Borer (Lepidoptera, Crambidae)

Abstract: Therophilus javanus is a koinobiont, solitary larval endoparasitoid currently being considered as a biological control agent against the pod borer Maruca vitrata, a devastating cowpea pest causing 20-80% crop losses in West Africa. We investigated ovary morphology and anatomy, oogenesis, potential fecundity, and egg load in T. javanus, as well as the effect of factors such as age of the female and parasitoid/host size at oviposition on egg load. The number of ovarioles was found to be variable and significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…On the other hand, some endoparasitoids can ensure the development of their progeny through maternal factors such as the venom fluid injected in the host at the time of parasitism 26 . Previous work has highlighted the presence of a venom gland attached to the reproductive tract of T. javanus females 4 and hypothesized that the venom fluid might be secreted in the host during parasitism 27 . Although the venom function has not been elucidated in more detail to date, we speculate it could regulate metabolic processes in parasitized M. vitrata caterpillars in order to affect its development and hence ensure complete development of the parasitoid larva 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, some endoparasitoids can ensure the development of their progeny through maternal factors such as the venom fluid injected in the host at the time of parasitism 26 . Previous work has highlighted the presence of a venom gland attached to the reproductive tract of T. javanus females 4 and hypothesized that the venom fluid might be secreted in the host during parasitism 27 . Although the venom function has not been elucidated in more detail to date, we speculate it could regulate metabolic processes in parasitized M. vitrata caterpillars in order to affect its development and hence ensure complete development of the parasitoid larva 28 .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that parasitizing early host stages can reduce the development time in koinobionts parasitoids 16 ; however, adult fitness of the offspring may be affected, in terms of short life expectancy, small size eggs, and reduced oviposition period 30 . Moreover, it has already been assessed that the development in early M. vitrata larval instars reduced the offspring potential fecundity in T. javanus 4 . Our observations further show that the sex-ratio of the offspring population was male-biased when stemming from three-day-old hosts, while the parasitoid produced more females when the oviposition occurred in four-day-old M. vitrata hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insect colonies were reared at the laboratories of the International Institute of Tropical Agriculture Benin (IITA-Benin) near Cotonou, Benin (12:12 L:D photoperiod; 26 °C ± 1.1 °C average temperature; 76% ± 7% relative humidity), with the methodology described in detail by Aboubakar Souna et al (2017) , and briefly summarized below.…”
Section: Methodsmentioning
confidence: 99%
“…Parallel studies investigating the reproductive potential of T. javanus have evidenced its considerable fecundity and suitability for mass rearing ( Aboubakar Souna et al, 2017 ). However, long-term reduction of M. vitrata populations depends mainly on how efficiently foraging T. javanus females will be able to detect and parasitize M. vitrata caterpillars throughout the cropping season and particularly during the offseason on alternative host plants.…”
Section: Introductionmentioning
confidence: 99%